Distributed Identity Authentication Mechanism in Networked Toll Systems Based on Blockchain Technology - Pu, Dayong; Li, Tao; Jin, Zhaoqi; Liu, Shihan; Yao, Xuegeng (Informatica, 2025)
With the development of the Internet of Things (IoT) and intelligent transportation systems, networked toll systems have become an essential part of modern traffic management. However, traditional identity authentication mechanisms rely on centralized trust institutions, which are prone to issues such as vulnerability to data storage attacks, identity information leakage, and poor interoperability between systems. These problems not only compromise the security and stability of toll systems but also risk user privacy and economic losses. To address these challenges, this paper proposes a distributed identity authentication mechanism based on blockchain technology. This mechanism leverages the decentralized, tamper-resistant, and smart contract features of blockchain technology to achieve an identity authentication process without the involvement of centralized institutions by storing user identity information in a distributed manner on the blockchain. The system utilizes distributed ledger technology to record identity authentication information across multiple nodes, thereby eliminating the risk of single-point failures and ensuring data consistency and integrity through consensus algorithms. Additionally, an automated identity authentication process based on smart contracts is designed to enable efficient identity verification between different networked toll subsystems, ensuring the security of the authentication process and consistency of user experience. The blockchain-based distributed identity authentication mechanism not only enhances the overall security level of networked toll systems but also provides a new solution for identity authentication in intelligent transportation systems.